The mTOR and total protein levels of stunted children - Andreinie, Ria; Mudjihartini, Ninik; Chandra, Dian Novita; Sekartini, Rini (Indonesian Pediatric Society, 2025)
Background Malnutrition is still a major health problem for children, with stunting being one of its manifestations. Human growth is in part controlled by the mammalian target of rapamycin (mTOR) pathway. Studies reviewing mTOR level and growth disorders in children are still limited and no research has described mTOR levels in stunted children in Indonesia. Objective To assess for a relationship between mTOR and total protein levels in blood plasma in stunted children aged 6-24 months and compare these levels with those in non-stunted children. Methods This case-control study was conducted in South Sumatra Province, Indonesia. Subjects were children aged 6-24 months. The inclusion criteria for the case group are children who have a length-for-age of <-2SD and the control group are children who have a body length according to age of more than or equal to -2 SD from the WHO growth standard chart. Anthropometric measurements were plotted on the WHO Growth Standards chart, while mTOR and total protein levels were measured using an ELISA method and spectrophotometry, respectively. Results Of 142 subjects, 71 children were allocated into each case and control group. Child characteristics that were significantly different between the two groups were age (P=0.002), birth length (P=0.012), weight-for-age Z-score (WAZ) (P<0.001), and body mass index (BMI) (P=0.015). WAZ status with the categories underweight and severely underweight had a higher risk of stunting. The mTOR and total protein levels between the two groups were not significantly different. Conclusion Further research is needed to explain the mechanism of mTOR signal deviations in children's growth and development, as mTOR and protein levels are not significantly different in stunted and non-stunted children.